Estimation of the transfer of vascular epiphytes, as a conservation strategy in the municipality of Aguazul, Casanare, Colombia. - Orozco Ávila, Javier; Valencia Marín, Argemiro; Betancur Pérez, Jhon Fredy (Revista de Investigación Agraria y Ambiental, 2017)
Epiphytes are plants that grow mainly attached to trunks, branches of trees and shrubs.  This research was conducted in the municipality of Aguazul, Casanare, Colombia, in order to evaluate conservation strategies through the transfer and recovery of vascular epiphytes. The selected population was 119 individuals. The variables were number of leaves, number of flowers, number of fruits, mortality rate, herbivory and associated entomofauna. The information collected was analyzed using descriptive statistics. As a result, it was found that the Bromeliaceae Family had the highest leaf development in the three monitorings. Bromeliaceae and Cactaceae Families did not present flowering and Orchidaceae presented low flowering. Fruiting had a similar behavior for these three families. Cactaceae Family did not present mortality, Orchidaceae recorded 2.02% and Bromeliaceae Family recorded 5.56% of mortality. As for herbivory, the orchid family filed a percentage of 0.06%; the Bromeliaceae  Family reported 0.11%, while the cactus family did not record any kind. The entomofauna was  found mainly in the Formicidae group for the three families, being the Cactaceae Family the one with a greater association, with 100%. According to the results, it is possible to move the vascular epiphytic species to new habitats, which makes it a viable alternative for revegetation of the affected area with conservation purposes.